Seaweed Diversity in Ekas Bay, East Lombok Regency, West Nusa Tenggara - Cokrowati, Nunik; Yatin, Nur; Affandi, Rangga Idris; Sumsanto, Muhammad; Yanti, Septiana Dwi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Seaweed is a fishery resource that has important economic value and is also an export commodity. Seaweed can be used as food directly. It is also used as raw material for medicine, cosmetics, bioethanol and bioenergy. Seaweed used as food, medicine and cosmetics has been cultivated. The types of seaweed that have been cultivated are still limited to three types, namely Kappaphycus alvarezii, Eucheuma spinosum and Gracilaria sp. Other species that live wild in marine waters have the potential to be utilized and developed through cultivation activities. Ekas Bay is a water body that has seaweed potential and is a location for seaweed cultivation. The purpose of this study was to analyze the types of seaweed that live in Ekas Bay, its antioxidant and chlorophyl. The research method used was purposive sampling method and experiment in the laboratory. The results of this study are the types of seaweed in Ekas Bay found in this study are Boergesenia sp., Turbinaria sp., Glacilaria sp., Hypnea sp., and Halymenea sp. The content of antioxidant and chlorophyl Borgesenia are 5,10% & 5,28 mg/L, Turbinaria sp. 25,94% & 14,42 mg/L, Gracilaria 1,99% & 4,3 mg/L, Hypnea sp 11,24% & 0,44 mg/L. Halymenia 1,79% & 8,83 mg/L and Sargassum 29,61% & 8,10 mg/L.